Pancreatico-pleural fistula mimicking a recurrent congenital diaphragmatic hernia: A case report - Maximilian Holweg; Justus Lieber; Alfred Königsrainer; Steffen Hartleif; Michael Esser; Jörg Fuchs (Journal of Pediatric Surgery Case Reports, 2024)
Introduction: Pancreaticopleural fistula (PPF) is a very rare complication of pancreatitis. The symptoms are non-specific and the diagnosis is often missed. Case presentation: A 14-year-old adolescent was admitted to the department of pediatric surgery with several readmissions due to recurrent left pleural effusion and chest pain. The patient also had a history of a left-sided congenital diaphragmatic hernia (CDH), which was surgically corrected via laparotomy at the age of two. The pleural effusion was explained in the context of pneumonia, but elevated serum levels of amylase and lipase prompted imaging. Computer tomography (CT) and standard magnetic resonance imaging (MRI) showed a small gap in the diaphragm and the pancreatic tail nearby leading to the diagnosis of recurrent CDH. Explorative thoracoscopy was performed, but showed the diaphragm intact. Pleurodesis was realized to treat the effusion. Two months later, recurrence of the pleural effusion in the left hemithorax and pancreatitis occurred. Magnetic resonance cholangiopancreatography (MRCP) showed a small subphrenic cyst close to the pancreatic tail and multiple supradiaphragmal cysts for the first time. Persistently, the small gap in the diaphragm close to the pancreatic tail was detected and the now suspected diagnosis was PPF. Subsequently, laparoscopic resection of the pancreatic tail was performed including the closure of the diaphragmatic gap. The course was uneventful, the pleural effusion disappeared, and the levels of serum pancreatic enzymes normalized during follow-up. Conclusion: PPF is rare and various entities may masquerade the diagnosis. A massive pleural effusion in combination with pancreatitis may indicate this serious condition.